Moving Genomics to Routine Care: An Initial Pilot in Acute Cardiovascular Disease. (October 2020) - Aryan, Zahra; Szanto, Attila; Pantazi, Angeliki; Reddi, Tejaswini; Rheinstein, Carolyn; Powers, Winslow; Wilson, Evan; Deo, Rahul C.; Chowdhury, Shimul; Salz, Lisa; Dimmock, David; Nahas, Shareef; et al.
Abstract : Background: Whole-genome sequencing (WGS) costs are falling, yet, outside oncology, this information is seldom used in adult clinics. We piloted a rapid WGS (rWGS) workflow, focusing initially on estimating power for a feasibility study of introducing genome information into acute cardiovascular care. Methods: A prospective implementation study was conducted to test the feasibility and clinical utility of rWGS in acute cardiovascular care. rWGS was performed on 50 adult patients with acute cardiovascular events and cardiac arrest survivors, testing for primary and secondary disease-causing variants, cardiovascular-related pharmacogenomics, and carrier status for recessive diseases. The impact of returning rWGS results on short-term clinical care of participants was investigated. The utility of polygenic risk scores to stratify coronary artery disease was also assessed. Results: Pathogenic variants, typically secondary findings, were identified in 20% (95% CI, 11.7–34.3). About 60% (95% CI, 46.2–72.4) of participants were carriers for one or more recessive traits, most commonly in HFE and SERPINA1 genes. Although 64% (95% CI, 50.1–75.9) of participants carried at least one pharmacogenetic variant of cardiovascular relevance, these were actionable in only 14% (95% CI, 7–26.2). Coronary artery disease prevalence among participants at the 95th percentile of polygenic risk score was 88.2% (95% CI, 71.8–95.7). Conclusions: We demonstrated the feasibility of rWGS integration into the inpatient management of adults with acute cardiovascular events. Our pilot identified pathogenic variants in one out of 5 acute vascular patients. Integrating rWGS in clinical care will progressively increase actionability. Abstract : Supplemental Digital Content is available in the text.